Preclinical evidence of probiotics in ulcerative colitis: a systematic review and network meta-analysis - Jin, Wenqin; Ai, Huangping; Huang, Qingqing; Li, Chuncai; He, Xiang; Jin, Zhao; Zuo, Yuling (Frontiers in Pharmacology, 2023)
The imbalance of gastrointestinal microbial composition has been identified as the main factor of chronic inflammatory diseases. At present, probiotics have a beneficial effect on the microbial composition of the human gastrointestinal tract, but it is still controversial and the specific mechanism is unknown. The purpose of this network meta-analysis is to compare the mechanism of different probiotics on ulcerative colitis. PubMed, Embase, and Web of Science were searched till 16 November 2022. The SYRCLE risk bias assessment tool was used to assess the quality of the research studies. A total of 42 studies, 839 ulcerative colitis models, and 24 kinds of probiotics were finally included. The results showed that L. rhamnosus has the best effect in relieving weight loss and improving the Shannon index in the ulcerative colitis model. E. faecium has the best effect in reducing colon injury; L. reuteri has the best effect in reducing the DAI; L. acidophilus has the best effect in reducing the HIS index and increasing the expression of tight junction protein ZO-1; and L. coryniformis has the best effect in reducing the content of serum pro-inflammatory factor TNF-α. It indicated that probiotics can improve ulcerative colitis by improving histopathological manifestations, reducing inflammatory reaction, and repairing the mucosal barrier, and different probiotics showed different effects. However, considering the limitations of this study, preclinical studies that require more large samples and high-quality and more reliable and rigorous experimental designs and reports need to be conducted in the future. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/#record details, identifier CRD42022383383.